Menglongshi 朦胧诗 dan Revolusi Kebudayaan Cina - Pulungsari, Rahadjeng (Paradigma: Jurnal Kajian Budaya, 2018)
Menglongshi (hanzi: 朦胧诗) or ‘misty poetry’ (also translated as ‘obscure poetry’) is one kind of Chinese poems created by young poets who experienced the Cultural Revolution in 1970s. The emergence of a new style of poetry which is different from the previous styles marked a new era of poetry writing in China. Its uniqueness lies in wordplay, metaphor, synesthesia, and symbols whose meanings cannot be easily identified. The misty poem also drew the cautious attention of the Chinese government, because the symbols and sequence of sentences were suspected to contain thoughts which are considered not in accordance with the government’s policies. Bei Dao and Gu Cheng were known as two of the most important misty poets. This paper analyzes two poems by Bei Dao and two poems by Gu Cheng in terms of their intrinsic elements, such as imagery and language style in order to interpret their meaning. Furthermore, in order to provide more supporting evidence, this research also analyzes the poems’ extrinsic elements to identify their respective meanings in a more comprehensive way. Therefore, the explanation for the occurrence of Cultural Revolution is a very important finding in this research. This study sought to explain the important role of misty poems in explaining the Cultural Revolution by examining Bei Dao and Gu Cheng’s works.